Strengthening Learning Priorities in the 21st Century: Review of Islamic Education Policy in Indonesia - Bima Fandi Asy'arie; Agung Heru Setiadi; Mochammad Firdaus; Rijal Mahdi; Moh. Aly Mustofa (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2024)
This research aims to identify and describe how Islamic education policies in Indonesia can be improved to suit the learning needs of the 21st century. This research is a type of library research with a qualitative approach. Data was obtained from three sources “Google Scholar” “ScienceDirect” and “RISE.” The discussion in this research highlights and contributes to the formulation of Islamic education policy to prioritize 21st-century learning, which includes building a commitment to mastering basic literacy and numeracy skills, measuring learning periodically, accurately, and relevantly, aligning the system with learning commitments, supporting teachers in the teaching and learning process, and adapting approaches in taking education policies. Apart from that, the agenda for formulating Islamic education policies must focus on these five priorities while maintaining Islamic religious values as the primary foundation. This study shows the importance of reform policies that focus on the use of technology in Islamic education, improving teacher quality, and digital-based innovative learning. Therefore, Islamic education policies in Indonesia must be designed objectively to create a generation that produces graduates with cognitive intelligence, strong character and morals, spiritual strength, and intellectual qualities that can compete on the global stage.